Composite membranes, methods of making and using the same

CN122937649APending Publication Date: 2026-10-20CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510465002.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-14
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0003]为了克服现有技术存在的气体分离膜无法平衡CO2渗透通量和选择性的问题,本发明提供一种复合膜及其制备方法与应用

Benefits of technology

[0015]本发明提供的复合膜中,支撑层具有适宜的连通密度、平均孔径和体积孔隙率,从而优化气体的传输路径,此外支撑层与分离层的界面结合力强,分离层的缺陷少,同时无需设置中间层,降低了复合膜的厚度。各方面结合,本发明提供的复合膜能够在保证所述复合膜选择性的同时提高渗透通量。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005359249720000121
    Figure BDA0005359249720000121
  • Figure BDA0005359249720000131
    Figure BDA0005359249720000131
  • Figure BDA0005359249720000231
    Figure BDA0005359249720000231
Patent Text Reader

Abstract

This invention relates to the field of gas separation membranes, specifically to a composite membrane, its preparation method, and its application. The composite membrane comprises a support layer and a separation layer sequentially arranged; the support layer has an average pore size of 20-120 nm and a volume porosity of 40-70%; the connectivity density of the support layer is 6 × 10⁻⁶. 15 -9×10 15 m ‑3 The composite membrane provided by this invention has a more suitable connectivity density in the support layer, stronger interfacial bonding between the support layer and the separation layer, and fewer defects in the separation layer. This allows the composite membrane provided by this invention to significantly improve CO2 permeation flux while maintaining high selectivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of gas separation membranes, and more specifically to a composite membrane, its preparation method, and its application. Background Technology

[0002] Polydimethylsiloxane (PDMS), as a representative membrane material with excellent permeability, has attracted widespread attention in gas separation, pervaporation, and nanofiltration. However, the fabrication of defect-free ultrathin PDMS membranes still faces significant challenges. On the one hand, the pore size, porosity, and thickness of the support layer membrane material itself are crucial factors affecting its gas permeation flux. On the other hand, to achieve higher gas permeability, the separation layer should be as thin as possible (<1 μm) during composite membrane preparation; an excessively thick separation layer leads to reduced membrane permeability and defects. To address this issue, some research groups have used highly permeable polymers or multiple inorganic materials to prepare an intermediate layer on the support surface, but this strategy complicates the membrane fabrication process. (Preparation and characterization of PDMS / zeolite4A / PAN mixed matrix thinfilm composite membrane for CO2 / N2 and CO2) 2 / CH4separations (Alavi, SA, Kargali, A., Sanaeepur, H., & Karimi, M. (2017). Research on Chemical Intermediates, 43, 2959-2984) discloses a novel composite membrane coated on a polyacrylonitrile ultrafiltration membrane support layer using polydimethylsiloxane / zeolite 4A (PDMS / zeolite 4A) as a mixed matrix thin separation layer. However, its CO2 permeation rate is only 3457 GPU, and its CO2 / N2 selectivity is 23.8. CN115155331A discloses a method for preparing a thin-film composite membrane using acryloyloxy-terminated PDMS. This method involves UV-induced monomer polymerization to form an ultrathin separation layer on the PAN surface, thus achieving the preparation of the PDMS thin-film composite membrane. However, this method has a complex membrane fabrication process, requiring strict control of UV irradiation time, temperature, and UV wavelength. The subsequent membrane also requires heat treatment at 80℃, making it difficult to control the membrane continuity. CN115608177A discloses a method for preparing and applying a polyether block polyamide / polydimethylsiloxane composite gas membrane. By introducing an amphoteric copolymer PDMSbPEO into the intermediate layer to improve interfacial compatibility with the separation layer, an ultrathin separation layer and a composite membrane with superior separation performance are obtained. However, controlling the viscosity of the intermediate layer casting solution is difficult, and gelation of the casting solution easily occurs, leading to a decrease in the gas permeation rate of the composite membrane. Furthermore, the membrane preparation process is complex, and there are still many problems in its application to industrial scale-up production. There is always a desire to improve membrane permeability, as higher permeability means less membrane area consumption, resulting in lower costs. Especially for CO2 capture in post-combustion flue gas, due to the low pressure and CO2 concentration of the feed gas, the gas separation membrane needs to possess both high selectivity and high permeability during flue gas carbon capture. However, the CO2 permeation rates of PDMS membranes reported in existing technologies are generally low. Summary of the Invention

[0003] To overcome the problem that existing gas separation membranes cannot balance CO2 permeation flux and selectivity, this invention provides a composite membrane, its preparation method, and its application.

[0004] To achieve the above objectives, the first aspect of the present invention provides a composite membrane, the composite membrane comprising a support layer and a separation layer disposed sequentially therefrom;

[0005] The average pore size of the support layer is 20-120 nm, and the volume porosity is 40-70%.

[0006] The connectivity density of the support layer is 6×10⁻⁶. 15 -9×10 15 m -3 .

[0007] A second aspect of the present invention provides a method for preparing a composite membrane, the method comprising the following steps:

[0008] (1) Apply a first casting solution containing a support layer material to form a first wet film;

[0009] (2) Spray one side of the first wet film for 1-25 seconds;

[0010] (3) The first wet film after spray treatment is first shaped to obtain a support layer;

[0011] (4) A second casting solution containing a separation layer material prepolymer, an organotin catalyst and a coupling agent is coated on the side of the support layer that has been sprayed to form a second wet film, and a second molding is performed to obtain the composite film.

[0012] A third aspect of the present invention provides a composite membrane prepared by the method provided in the second aspect of the present invention.

[0013] The fourth aspect of the present invention provides an application of the composite membrane provided in the first or third aspect of the present invention in gas separation.

[0014] The composite membrane, its preparation method, and its application provided by this invention have the following beneficial technical effects:

[0015] In the composite membrane provided by this invention, the support layer has suitable connectivity density, average pore size, and volumetric porosity, thereby optimizing the gas transport path. Furthermore, the interfacial bonding between the support layer and the separation layer is strong, the separation layer has few defects, and an intermediate layer is unnecessary, reducing the thickness of the composite membrane. Combined, the composite membrane provided by this invention can improve permeation flux while maintaining the selectivity of the composite membrane.

[0016] In the composite membrane preparation method provided by the present invention, the pore structure of the support layer can be effectively improved by spraying for 1-25 seconds, thereby improving the connectivity density, average pore size and volume porosity of the support layer. It can also enhance the interfacial bonding force between the support layer and the separation layer, reduce defects in the separation layer, and eliminate the need for an intermediate layer in the composite membrane, thus reducing the thickness of the composite membrane. Attached Figure Description

[0017] Figure 1 The images shown are SEM images of the PAN support layer obtained in Example 1 of the present invention, where (a) is a surface SEM image and (b) is a cross-sectional SEM image.

[0018] Figure 2 Here are SEM images of the composite membrane prepared in Example 1 of the present invention, where (a) is a surface SEM image and (b) is a cross-sectional SEM image.

[0019] Figure 3 The images shown are SEM images of the PAN support layer obtained in Example 5 of the present invention, where (a) is a surface SEM image and (b) is a cross-sectional SEM image.

[0020] Figure 4 Here are SEM images of the composite membrane prepared in Example 5 of the present invention, where (a) is a surface SEM image and (b) is a cross-sectional SEM image.

[0021] Figure 5 The images shown are SEM images of the PAN support layer prepared in Comparative Example 1 of the present invention, where (a) is a surface SEM image and (b) is a cross-sectional SEM image.

[0022] Figure 6 The images shown are SEM images of the PAN support layer prepared in Comparative Example 3 of the present invention, where (a) is a surface SEM image and (b) is a cross-sectional SEM image.

[0023] Figure 7 This is a magnified SEM image of the cross-section of the PAN support layer obtained in Comparative Example 3.

[0024] Figure 8 This is the nano-infrared spectrum (Nano-IR) of the PAN support layer and composite film prepared in this invention. Detailed Implementation

[0025] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0026] The first aspect of the present invention provides a composite membrane, the composite membrane comprising a support layer and a separation layer disposed sequentially;

[0027] The average pore size of the support layer is 20-120 nm, and the volume porosity is 40-70%.

[0028] The connectivity density of the support layer is 6×10⁻⁶. 15 -9×10 15 m -3 .

[0029] In the composite membrane provided by the present invention, the support layer has a suitable connectivity density, average pore size and volumetric porosity, thereby optimizing the gas transport path. In addition, the interfacial bonding force between the support layer and the separation layer is strong and the separation layer has few defects. The combination of these two aspects can improve the permeation flux while ensuring the selectivity of the composite membrane.

[0030] According to the present invention, preferably, the average pore size of the support layer is 40-85 nm.

[0031] In this invention, when the average pore size of the support layer is within the above-mentioned range, it can provide more gas transmission channels, further reduce the gas mass transfer resistance of the support layer, and thus improve the overall permeation flux of the composite membrane.

[0032] According to the present invention, preferably, the volumetric porosity of the support layer is 50-60%.

[0033] In this invention, when the volume porosity of the support layer is within the above-mentioned range, the selectivity and permeation flux of the composite membrane can be better balanced.

[0034] According to a particularly preferred embodiment of the present invention, the average pore size of the support layer is 40-85 nm, and the volume porosity of the support layer is 50-60%.

[0035] In this invention, the volume porosity and average pore size of the support layer simultaneously meet the above-mentioned particularly preferred ranges, which can further improve the gas permeation rate of the composite membrane.

[0036] According to a preferred embodiment of the present invention, the connectivity density of the support layer is 6.5 × 10⁻⁶. 15 -8.5×10 15 m -3 .

[0037] In this invention, when the connectivity density of the support layer is within the above-mentioned preferred range, the selectivity and permeation flux of the composite membrane can be better balanced.

[0038] According to the present invention, preferably, the D of the support layer 10 Aperture is 19-39 nm, D 50 Aperture is 40-95nm, D 90 The pore size is 100-150nm.

[0039] In this invention, D 10 Aperture refers to the volume of pores with a diameter less than or equal to this value that constitutes 10% of the total pore volume in the pore size distribution; D 50 Aperture refers to the volume of pores with a diameter less than or equal to this value that constitutes 50% of the total pore volume in a pore size distribution; D 90 Aperture refers to the volume of pores with a diameter less than or equal to the specified value in the aperture distribution, which accounts for 90% of the total pore volume.

[0040] In this invention, when the pore size distribution of the support layer is within the above-mentioned range, it can further provide an optimized gas transport channel, reduce the gas mass transfer resistance of the support layer, thereby increasing the permeation flux of the composite membrane while ensuring a certain degree of selectivity.

[0041] More preferably, the D of the support layer 10 Aperture is 20-35nm, D 50 Aperture is 42-85nm, D 90 The aperture is 103-135nm.

[0042] According to the present invention, preferably, the thickness of the support layer is 10-60 μm.

[0043] In this invention, when the thickness of the support layer is within the above-mentioned range, the gas mass transfer resistance can be further reduced, thereby increasing the permeation flux of the composite membrane.

[0044] More preferably, the thickness of the support layer is 20-40 μm.

[0045] According to a preferred embodiment of the present invention, the thickness of the separation layer is 100-400 nm.

[0046] In this invention, when the thickness of the separation layer is within the above-mentioned range, the selectivity of the composite membrane can be improved while ensuring a certain permeation flux.

[0047] More preferably, the thickness of the separation layer is 150-350 nm.

[0048] Because of the strong interfacial bonding between the support layer and the separation layer, according to a preferred embodiment of the present invention, the composite membrane does not contain an intermediate layer, thereby reducing the thickness of the composite membrane.

[0049] According to the present invention, preferably, the average roughness of the surface of the separation layer is 5-10 nm.

[0050] In this invention, when the average roughness of the separation layer surface is within the above-mentioned range, there are fewer surface defects, which can further improve the selectivity of the composite film.

[0051] More preferably, the average roughness of the separation layer surface is 8-10 nm.

[0052] According to the present invention, preferably, the water contact angle of the separation layer is 100-115°.

[0053] In this invention, when the water contact angle of the separation layer is within the above-mentioned range, it also indicates that the separation layer has fewer defects, which can further improve the selectivity of the composite membrane.

[0054] More preferably, the water contact angle of the separation layer is 108-115°.

[0055] According to a particularly preferred embodiment of the present invention, the average roughness of the surface of the separation layer is 8-10 nm, and the water contact angle is 108-115°.

[0056] In this invention, when the average roughness of the separation layer surface and the water contact angle simultaneously meet the above-mentioned particularly preferred ranges, the selectivity of the composite membrane can be further improved.

[0057] According to the present invention, preferably, the CO2 permeation rate of the composite membrane is 10000-18000 GPU, and the ideal gas separation coefficient of CO2 / N2 is 9-13.

[0058] More preferably, the CO2 permeation rate of the composite membrane is 15000-18000 GPU, and the ideal gas separation coefficient of CO2 / N2 is 10-13.

[0059] According to a preferred embodiment of the present invention, the support layer is selected from at least one of polysulfone, polyethersulfone, polyacrylonitrile, cellulose acetate, polyvinylidene fluoride, polyimide, polyacrylic acid, polylactic acid, polyamide, polyetherimide, polystyrene, polyolefin, and polyester.

[0060] More preferably, the support layer is polyacrylonitrile (PAN).

[0061] In this invention, polyacrylonitrile can form films better and is easier to process. Moreover, thanks to the polar cyano group in its molecular structure, it has high selectivity for CO2 and can form a strong interaction with CO2 molecules, which is beneficial to the separation of CO2.

[0062] More preferably, the number average molecular weight of the polyacrylonitrile is 70,000-100,000 Da.

[0063] According to the present invention, preferably, the separation layer is a polysiloxane and / or a polysilyne.

[0064] More preferably, the separation layer is a polysiloxane.

[0065] In this invention, polysiloxane can provide a smooth and flat membrane surface, which reduces the mass transfer resistance to gas molecules, thereby further improving the gas permeation flux of the composite membrane.

[0066] More preferably, the separation layer is polydimethylsiloxane (PDMS).

[0067] According to one specific embodiment of the present invention, the composite membrane further comprises a substrate layer, wherein the separation layer, the support layer, and the substrate layer are disposed sequentially. The present invention does not particularly limit the specific type of the substrate layer, and those skilled in the art can conventionally select one. For example, the substrate layer can be at least one of nonwoven fabric, woven fabric, polyester screen, and electrospun membrane.

[0068] Specifically, the thickness of the substrate layer is 85-100 μm.

[0069] A second aspect of the present invention provides a method for preparing a composite membrane, the method comprising the following steps:

[0070] (1) Apply a first casting solution containing a support layer material to form a first wet film;

[0071] (2) Spray one side of the first wet film for 1-25 seconds;

[0072] (3) The first wet film after spray treatment is first shaped to obtain a support layer;

[0073] (4) A second casting solution containing a separation layer material prepolymer, an organotin catalyst and a coupling agent is coated on the side of the support layer that has been sprayed to form a second wet film, and a second molding is performed to obtain the composite film.

[0074] This invention achieves the following beneficial technical effects by spraying the first wet film:

[0075] In the composite membrane preparation method provided by the present invention, the pore structure of the support layer can be effectively improved by spraying for 1-25 seconds, thereby improving the connectivity density, average pore size and volume porosity of the support layer. It can also enhance the interfacial bonding force between the support layer and the separation layer, reduce defects in the separation layer, and eliminate the need for an intermediate layer in the composite membrane, thus reducing the thickness of the composite membrane.

[0076] According to a preferred embodiment of the present invention, in step (1), the support layer material is selected from at least one of polysulfone, polyethersulfone, polyacrylonitrile, cellulose acetate, polyvinylidene fluoride, polyimide, polyacrylic acid, polylactic acid, polyamide, polyetherimide, polystyrene, polyolefin, and polyester.

[0077] The present invention improves the interfacial bonding force between the support layer and the separation layer by spraying the first wet film, thus eliminating the need for an intermediate layer and reducing the thickness of the composite film.

[0078] More preferably, the support layer material is polyacrylonitrile.

[0079] According to the present invention, preferably, the thickness of the first wet film is 70-100 μm.

[0080] More preferably, the thickness of the first wet film is 80-90 μm.

[0081] According to the present invention, preferably, the concentration of the support layer material in the first casting solution is 6-15 wt%.

[0082] In this invention, when the concentration of the support layer material in the first casting solution is within the above-mentioned range, the resulting support layer has a more suitable average pore size and volumetric porosity.

[0083] More preferably, the concentration of the support layer material in the first casting solution is 8-12 wt%.

[0084] The present invention does not particularly limit the specific type of solvent in the first casting solution, and those skilled in the art can select the solvent accordingly based on different support layer materials. The solvent in the first casting solution can be at least one selected from N-methylformamide, N,N-dimethylformamide, N,N-dimethylacetamide, acetone, dimethyl sulfoxide, tetramethyl sulfoxide, tetrahydrofuran, chloroform, triethyl phosphate, trimethyl phosphate, hexamethylammonium phosphate, toluene, hexane, and octane.

[0085] In this invention, the preparation of the first casting solution can be carried out under heating conditions, such as 55-65°C, to promote the dissolution of the support layer material.

[0086] According to the present invention, preferably, the first casting solution is degassed before coating.

[0087] According to a preferred embodiment of the present invention, in step (2), the spray treatment time is 1-20 seconds.

[0088] In this invention, the spray treatment time has a significant impact on the permeability and selectivity of the composite membrane. When the spray treatment time is within the above-mentioned range, the resulting composite membrane has better permeability and selectivity.

[0089] According to the present invention, preferably, in step (2), the side of the first wet film that is not sprayed is protected, and the specific method of protection may be shielding and / or blowing air.

[0090] According to the present invention, preferably, the atomization amount of the spray treatment is 2.5-20 L·m -2 ·h -1 .

[0091] In this invention, when the atomization amount of the spray treatment is within the above-mentioned range, the spray treatment has a better effect and can make the continuous network pore structure in the obtained support layer more uniform.

[0092] More preferably, the atomization rate of the spray treatment is 5-15 L·m -2 ·h -1 .

[0093] According to the present invention, preferably, the liquid used in the spray treatment is a non-solvent of the support layer material, such as water and / or lower alcohols.

[0094] The present invention does not particularly limit the specific method of atomizing the liquid used in spray treatment. Those skilled in the art can choose conventionally, such as at least one of pressure atomization, rotary atomization, high-pressure airflow atomization and ultrasonic atomization.

[0095] The present invention does not particularly limit the specific method of the first molding, and those skilled in the art can choose conventionally.

[0096] According to one specific embodiment of the present invention, the first molding method is non-solvent-induced phase separation.

[0097] According to a preferred embodiment of the present invention, in step (4), the prepolymer of the separation layer material is a polysiloxane prepolymer and / or a polysilyne prepolymer.

[0098] According to the present invention, preferably, the concentration of the prepolymer of the separation layer material in the second casting solution is 0.2-3 wt%.

[0099] In this invention, when the concentration of the prepolymer of the separation layer material in the second casting solution is within the above-mentioned range, the fluidity and film-forming properties of the second casting solution are better, and it can be better spread on the support layer.

[0100] More preferably, the concentration of the prepolymer of the separation layer material in the second casting solution is 0.2-2 wt%.

[0101] The present invention does not particularly limit the specific type of the organotin catalyst, and those skilled in the art can choose conventionally.

[0102] According to the present invention, preferably, the organotin catalyst is selected from at least one of dibutyltin diacetate, dibutyltin dilaurate, and stannous octoate.

[0103] Preferably, the concentration of the organotin catalyst in the second casting solution is 0.1-2.5 wt%.

[0104] More preferably, the concentration of the organotin catalyst in the second casting solution is 0.15-2 wt%.

[0105] The present invention does not particularly limit the specific type of coupling agent, and those skilled in the art can choose conventionally.

[0106] According to the present invention, preferably, the coupling agent is selected from at least one of γ-aminopropyltriethoxysilane, vinyltrimethoxysilane, tetraethoxysilane, methyltriethoxysilane and propyltriethoxysilane.

[0107] Preferably, the concentration of the coupling agent in the second casting solution is 0.1-2.5 wt%.

[0108] More preferably, the concentration of the coupling agent in the second casting solution is 0.15-2 wt%.

[0109] According to one specific embodiment of the present invention, the solvent in the second casting solution is selected from at least one of n-hexane, n-heptane, toluene, dichloromethane, and chloroform.

[0110] According to the present invention, preferably, the thickness of the second wet film is 1-3 μm.

[0111] More preferably, the thickness of the second wet film is 1-2 μm.

[0112] According to the present invention, preferably, the second casting solution is degassed before coating.

[0113] According to the present invention, preferably, the second molding condition is drying at 20-50°C for 30-60 minutes.

[0114] According to a preferred embodiment of the present invention, the second casting solution is obtained by mixing a separation layer material prepolymer, an organotin catalyst and a coupling agent in the presence of a solvent to obtain a relatively concentrated solution, and then diluting it to a concentration of 0.2-2 wt% of the separation layer material prepolymer.

[0115] According to a further preferred embodiment of the present invention, the second casting solution is prepared by mixing a separation layer material prepolymer, an organotin catalyst, and a coupling agent in the presence of a solvent to obtain a solution with a separation layer material prepolymer concentration of 1-2 wt%, an organotin catalyst concentration of 0.8-1.6 wt%, and a coupling agent concentration of 0.8-1.6 wt%, and then adding the solvent to dilute to a separation layer material prepolymer concentration of 0.2-0.5 wt%, an organotin catalyst concentration of 0.16-0.4 wt%, and a coupling agent concentration of 0.16-0.4 wt%, thus obtaining the second casting solution.

[0116] In this invention, the further preferred configuration of the second casting solution can further control the viscosity of the second casting solution, thereby extending the gel time of the casting solution and facilitating the continuity of the coating process.

[0117] According to a preferred embodiment of the present invention, the method further includes: pre-filling the side of the support layer that has been sprayed with a filling liquid before applying the second casting liquid.

[0118] In this invention, pre-filling can further improve the permeability of the composite membrane, while reducing the decrease in selectivity caused by defects in the separation layer.

[0119] More preferably, the filling liquid is selected from at least one of water, lower alcohols, lower ethers, N-methylpyrrolidone and N,N-dimethylformamide.

[0120] According to a particularly preferred embodiment of the present invention, step (4) further includes, after the second molding, coating the surface of the separation layer obtained by the second molding with a third casting solution containing a separation layer material prepolymer, an organotin catalyst and a coupling agent to form a third wet film, and performing a third molding to obtain the composite film.

[0121] In this invention, the third molding process can further improve the CO2 / N2 selectivity of the composite membrane.

[0122] Preferably, the concentration of the organotin catalyst in the third casting solution is 0.1-2.5 wt%.

[0123] More preferably, the concentration of the organotin catalyst in the third casting solution is 0.15-2 wt%. The present invention does not particularly limit the specific type of coupling agent, and those skilled in the art can choose conventionally.

[0124] Preferably, the concentration of the coupling agent in the third casting solution is 0.1-2.5 wt%.

[0125] More preferably, the concentration of the coupling agent in the third casting solution is 0.15-2 wt%.

[0126] According to one specific embodiment of the present invention, the solvent in the third casting solution is selected from at least one of n-hexane, n-heptane, toluene, dichloromethane, and chloroform.

[0127] According to the present invention, preferably, the thickness of the third wet film is 1-3 μm.

[0128] More preferably, the thickness of the third wet film is 1-2 μm.

[0129] According to the present invention, preferably, the third casting solution is degassed before coating.

[0130] According to the present invention, preferably, the third molding condition is drying at 20-50°C for 30-60 minutes.

[0131] According to a preferred embodiment of the present invention, the third casting solution is obtained by mixing a separation layer material prepolymer, an organotin catalyst and a coupling agent in the presence of a solvent to obtain a relatively concentrated solution, and then diluting it to a concentration of 0.2-2 wt% of the separation layer material prepolymer.

[0132] According to a further preferred embodiment of the present invention, the preparation method of the third casting solution includes mixing a separation layer material prepolymer, an organotin catalyst, and a coupling agent in the presence of a solvent to obtain a solution with a separation layer material prepolymer concentration of 1-2 wt%, an organotin catalyst concentration of 0.8-1.6 wt%, and a coupling agent concentration of 0.8-1.6 wt%, and then adding the solvent to dilute to a separation layer material prepolymer concentration of 0.2-0.5 wt%, an organotin catalyst concentration of 0.16-0.4 wt%, and a coupling agent concentration of 0.16-0.4 wt%, thus obtaining the third casting solution.

[0133] In this invention, the further preferred configuration of the third casting solution can further control the viscosity of the third casting solution, prolong the gel time of the casting solution, and facilitate the continuity of the coating process.

[0134] A third aspect of the present invention provides a composite membrane prepared by the method provided in the second aspect of the present invention.

[0135] The fourth aspect of the present invention provides an application of the composite membrane provided in the first or third aspect of the present invention in gas separation.

[0136] The present invention will be described in detail below through embodiments.

[0137] In the following embodiments, the volumetric porosity of the support layer was determined by weighing:

[0138]

[0139] Among them, W d The mass of the dried support layer is expressed in g.

[0140] W w The mass of the support layer after liquid absorption is in grams.

[0141] ρ L The density of the liquid is expressed in g / cm³. 3 ;

[0142] ρ m The density of the support layer is in g / cm³. 3 .

[0143] Average pore size of the support layer, D 10 Aperture, D 50 Aperture and D 90The pore size was obtained using a Beishide BSD-660S pore size analyzer;

[0144] The supporting layer was scanned using a Bruker SkysCan 2211 high-resolution X-ray CT scanner with a sample size of 5×5mm, a resolution of 300nm, and LED voltage and current of 40kV and 500μA. The connectivity density of the supporting layer was calculated using CTan software.

[0145] The average roughness of the separation layer surface was determined using a Bruker Corp nanoIR3 nanometer infrared spectrometer.

[0146] The water contact angle of the separation layer was measured using a KRUSSDSA 100 contact angle meter;

[0147] The thicknesses of the support layer and the separation layer were measured using a Mitutoyo 547-401 high-precision thickness gauge.

[0148] The thickness of the wet film was measured using a toothed gauge;

[0149] The CO2 and N2 permeation rates of the composite membrane are calculated as follows:

[0150]

[0151] Where J represents the penetration rate, GPU;

[0152] F is the gas flow rate, in cm. 3 / s;

[0153] A is the effective area of ​​the membrane, in cm² 2 ;

[0154] ΔP is the transmembrane pressure difference, in cmHg;

[0155] CO2 pure gas and N2 pure gas were used as raw materials, and the gas flow rate F was measured using a soap film flow meter.

[0156] The ideal CO2 / N2 separation coefficient of the composite membrane is the ratio of the gas permeation rate of pure CO2 gas to the gas permeation rate of pure N2 gas.

[0157] The PDMS prepolymer was purchased from Shandong Dayi Chemical Co., Ltd., brand name DY-107.

[0158] Unless otherwise specified, all other reagents and raw materials are commercially available.

[0159] Example 1

[0160] (1) Dissolve 10g of polyacrylonitrile in 90g of N,N-dimethylformamide solvent, stir at 50℃ to form a homogeneous solution, and degas under vacuum to obtain the first casting solution. Use a continuous coating machine to coat the first casting solution onto a nonwoven fabric to form a first wet film with a thickness of 85μm.

[0161] (2) After ultrasonically atomizing the deionized water, spray it onto the side of the first wet film not covered by the nonwoven fabric. The atomization time is 5 seconds and the atomization volume is 10 L·m. -2 ·h -1 A glass plate is used to protect the nonwoven fabric side of the first wet film from contact with the mist droplets.

[0162] (3) The first wet film after spray treatment is immersed in a deionized water coagulation bath for 3 minutes for the first molding. After washing with deionized water, the support layer is obtained.

[0163] (4) Dissolve 0.5g of PDMS prepolymer, 0.4g of tetraethoxysilane, and 0.4g of dibutyltin dilaurate in 98.7g of n-heptane solvent, stir at 30°C to form a homogeneous solution, and degas under vacuum to obtain a second casting solution with a PDMS prepolymer concentration of 0.5wt%. Wet the support layer with deionized water, and then use a continuous coating machine to coat the second casting solution onto the side of the support layer not covered with nonwoven fabric to form a second wet film with a thickness of 2μm. Dry in a 30°C oven for 30min to obtain the composite film.

[0164] Example 2

[0165] (1) Dissolve 10g of polyacrylonitrile in 90g of N,N-dimethylformamide solvent, stir at 50℃ to form a homogeneous solution, and degas under vacuum to obtain the first casting solution. Use a continuous coating machine to coat the first casting solution onto a nonwoven fabric to form a first wet film with a thickness of 85μm.

[0166] (2) After ultrasonically atomizing the deionized water, spray it onto the side of the first wet film not covered by the nonwoven fabric. The atomization time is 5 seconds and the atomization volume is 6.5 L·m -2 ·h -1 A glass plate is used to protect the nonwoven fabric side of the first wet film from contact with the mist droplets.

[0167] (3) The first wet film after spray treatment is immersed in a deionized water coagulation bath for 3 minutes for the first molding. After washing with deionized water, the support layer is obtained.

[0168] (4) Dissolve 2g of PDMS prepolymer, 1.6g of tetraethoxysilane, and 1.6g of dibutyltin dilaurate in 94.8g of n-heptane solvent, stir at 30°C to form a homogeneous solution, and degas under vacuum to obtain a solution with a PDMS prepolymer concentration of 2wt%. Dilute the solution to a PDMS prepolymer concentration of 0.5wt% to obtain a second casting solution. Wet the support layer with deionized water, and then use a continuous coating machine to coat the second casting solution onto the side of the support layer not covered with nonwoven fabric to form a second wet film with a thickness of 2μm. Dry the film in a 30°C oven for 30min to obtain the composite film.

[0169] Example 3

[0170] (1) Dissolve 10g of polyacrylonitrile in 90g of N,N-dimethylformamide solvent, stir at 50℃ to form a homogeneous solution, and degas under vacuum to obtain the first casting solution. Use a continuous coating machine to coat the first casting solution onto a nonwoven fabric to form a first wet film with a thickness of 85μm.

[0171] (2) After ultrasonically atomizing the deionized water, spray it onto the side of the first wet film not covered by the nonwoven fabric. The atomization time is 5 seconds and the atomization volume is 10 L·m. -2 ·h -1 A glass plate is used to protect the nonwoven fabric side of the first wet film from contact with the mist droplets.

[0172] (3) The first wet film after spray treatment is immersed in a deionized water coagulation bath for 3 minutes for the first molding. After washing with deionized water, the support layer is obtained.

[0173] (4) Dissolve 1g of PDMS prepolymer, 0.5g of tetraethoxysilane, and 0.5g of dibutyltin dilaurate in 98g of n-heptane solvent, stir at 30°C to form a homogeneous solution, and degas under vacuum to obtain a solution with a PDMS prepolymer concentration of 1wt%. Then dilute the solution to a PDMS prepolymer concentration of 0.2wt% to obtain a second casting solution. Wet the support layer with deionized water, and then use a continuous coating machine to coat the second casting solution onto the side of the support layer not covered by the nonwoven fabric to form a second wet film with a thickness of 1μm. Dry the film in a 30°C oven tunnel for 30min.

[0174] Then, a second casting liquid was applied to the surface of the already formed separation layer using a continuous coating machine to form a third wet film with a thickness of 1 μm. The film was then dried in a 30°C oven for 30 min and then dried again in a 30°C oven for 30 min to obtain the composite film.

[0175] Example 4

[0176] (1) Dissolve 10g of polyacrylonitrile in 90g of N,N-dimethylformamide solvent, stir at 50℃ to form a homogeneous solution, and degas under vacuum to obtain the first casting solution. Use a continuous coating machine to coat the first casting solution onto a nonwoven fabric to form a first wet film with a thickness of 85μm.

[0177] (2) After ultrasonically atomizing the deionized water, spray it onto the side of the first wet film not covered by the nonwoven fabric. The atomization time is 5 seconds and the atomization volume is 10 L·m. -2 ·h -1 A glass plate is used to protect the nonwoven fabric side of the first wet film from contact with the mist droplets.

[0178] (3) The first wet film after spray treatment is immersed in a deionized water coagulation bath for 3 minutes for the first molding. After washing with deionized water, the support layer is obtained.

[0179] (4) Dissolve 1g of PDMS prepolymer, 0.5g of tetraethoxysilane, and 0.5g of dibutyltin dilaurate in 98g of n-heptane solvent, stir at 30°C to form a homogeneous solution, and degas under vacuum to obtain a solution with a PDMS prepolymer concentration of 1wt%. Then dilute the solution to PDMS prepolymer concentrations of 0.2wt% and 0.5wt% respectively to obtain a second casting solution and a third casting solution. Wet the support layer with deionized water, and then use a continuous coating machine to coat the second casting solution onto the side of the support layer not covered with nonwoven fabric to form a second wet film with a thickness of 1μm. Dry in a 30°C oven tunnel for 30min.

[0180] Then, a third casting solution was coated onto the surface of the already formed separation layer using a continuous coating machine to form a third wet film with a thickness of 1 μm. The film was then dried in a 30°C oven for 30 min and then dried again in a 30°C oven for 30 min to obtain the composite film.

[0181] Example 5

[0182] (1) Dissolve 10g of polyacrylonitrile in 90g of N,N-dimethylformamide solvent, stir at 50℃ to form a homogeneous solution, and degas under vacuum to obtain the first casting solution. Use a continuous coating machine to coat the first casting solution onto a nonwoven fabric to form a first wet film with a thickness of 85μm.

[0183] (2) After ultrasonically atomizing the deionized water, spray it onto the side of the first wet film not covered by the nonwoven fabric. The atomization time is 10 seconds and the atomization volume is 5 L·m. -2 ·h -1 A glass plate is used to protect the nonwoven fabric side of the first wet film from contact with the mist droplets.

[0184] (3) The first wet film after spray treatment is immersed in a deionized water coagulation bath for 3 minutes for the first molding. After washing with deionized water, the support layer is obtained.

[0185] (4) Dissolve 0.5g of PDMS prepolymer, 0.4g of tetraethoxysilane and 0.4g of dibutyltin dilaurate in 98.7g of n-heptane solvent, stir at 30°C to form a uniform solution, and degas under vacuum to obtain a second casting solution with a PDMS prepolymer concentration of 0.5wt%.

[0186] The support layer is wetted with deionized water, and then the second casting solution is applied to the side of the support layer not covered with nonwoven fabric using a continuous film scraper to form a second wet film with a thickness of 2μm. The film is then dried in a 30°C oven for 30 minutes to obtain the composite film.

[0187] Example 6

[0188] (1) Dissolve 10g of polyacrylonitrile in 90g of N,N-dimethylformamide solvent, stir at 50℃ to form a homogeneous solution, and degas under vacuum to obtain the first casting solution. Use a continuous coating machine to coat the first casting solution onto a nonwoven fabric to form a first wet film with a thickness of 85μm.

[0189] (2) After ultrasonically atomizing the deionized water, spray it onto the side of the first wet film not covered by the nonwoven fabric. The atomization time is 10s and the atomization volume is 10L·m -2 ·h -1 A glass plate is used to protect the nonwoven fabric side of the first wet film from contact with the mist droplets.

[0190] (3) The first wet film after spray treatment is immersed in a deionized water coagulation bath for 3 minutes for the first molding. After washing with deionized water, the support layer is obtained.

[0191] (4) Dissolve 1g of PDMS prepolymer, 0.5g of tetraethoxysilane and 0.5g of dibutyltin dilaurate in 98g of n-heptane solvent, stir at 30°C to form a uniform solution, remove bubbles under vacuum to obtain a solution with a PDMS prepolymer concentration of 1wt%, and then dilute it to a PDMS prepolymer concentration of 0.5wt% to obtain the second casting solution.

[0192] The support layer is wetted with deionized water, and then the second casting solution is applied to the side of the support layer not covered with nonwoven fabric using a continuous film scraper to form a second wet film with a thickness of 2μm. The film is then dried in a 30°C oven for 30 minutes to obtain the composite film.

[0193] Example 7

[0194] (1) Dissolve 10g of polyacrylonitrile in 90g of N,N-dimethylformamide solvent, stir at 50℃ to form a homogeneous solution, and degas under vacuum to obtain the first casting solution. Use a continuous coating machine to coat the first casting solution onto a nonwoven fabric to form a first wet film with a thickness of 85μm.

[0195] (2) After ultrasonically atomizing the deionized water, spray it onto the side of the first wet film not covered by the nonwoven fabric. The atomization time is 10s and the atomization volume is 15L·m. -2 ·h -1 A glass plate is used to protect the nonwoven fabric side of the first wet film from contact with the mist droplets.

[0196] (3) The first wet film after spray treatment is immersed in a deionized water coagulation bath for 3 minutes for the first molding. After washing with deionized water, the support layer is obtained.

[0197] (4) Dissolve 1g of PDMS prepolymer, 0.5g of tetraethoxysilane, and 0.5g of dibutyltin dilaurate in 98g of n-heptane solvent, stir at 30°C to form a homogeneous solution, and degas under vacuum to obtain a solution with a PDMS prepolymer concentration of 1wt%. Then dilute the solution to a PDMS prepolymer concentration of 0.2wt% to obtain a second casting solution. Wet the support layer with deionized water, and then use a continuous coating machine to coat the second casting solution onto the side of the support layer not covered by the nonwoven fabric to form a second wet film with a thickness of 1μm. Dry the film in a 30°C oven tunnel for 30min.

[0198] Then, a second casting liquid was applied to the surface of the already formed separation layer using a continuous coating machine to form a third wet film with a thickness of 1 μm. The film was then dried in a 30°C oven for 30 min and then dried again in a 30°C oven for 30 min to obtain the composite film.

[0199] Example 8

[0200] (1) Dissolve 10g of polyacrylonitrile in 90g of N,N-dimethylformamide solvent, stir at 50℃ to form a homogeneous solution, and degas under vacuum to obtain the first casting solution. Use a continuous coating machine to coat the first casting solution onto a nonwoven fabric to form a first wet film with a thickness of 85μm.

[0201] (2) After ultrasonically atomizing the deionized water, spray it onto the side of the first wet film not covered by the nonwoven fabric. The atomization time is 10s and the atomization volume is 12L·m. -2 ·h -1 A glass plate is used to protect the nonwoven fabric side of the first wet film from contact with the mist droplets.

[0202] (3) The first wet film after spray treatment is immersed in a deionized water coagulation bath for 3 minutes for the first molding. After washing with deionized water, the support layer is obtained.

[0203] (4) Dissolve 0.2g of PDMS prepolymer, 0.1g of tetraethoxysilane and 0.1g of dibutyltin dilaurate in 99.6g of n-heptane solvent, stir at 30°C to form a uniform solution, and degas under vacuum to obtain a second casting solution with a PDMS prepolymer concentration of 0.2wt%.

[0204] The support layer is wetted with deionized water, and then the second casting solution is applied to the side of the support layer not covered with nonwoven fabric using a continuous film scraper to form a second wet film with a thickness of 1 μm. The film is then dried in a 30°C oven for 30 min.

[0205] Then, a second casting liquid was applied again to the surface of the already formed separation layer using a continuous coating machine to form a third wet film with a thickness of 1 μm. The film was then dried in a 30°C oven for 30 min and then dried again in a 30°C oven for 30 min to obtain the composite film.

[0206] Example 9

[0207] (1) Dissolve 8g of polyacrylonitrile in 92g of N,N-dimethylformamide solvent, stir at 50℃ to form a homogeneous solution, and remove bubbles under vacuum to obtain the first casting solution. Use a continuous coating machine to coat the first casting solution onto a nonwoven fabric to form a first wet film with a thickness of 85μm.

[0208] (2) After ultrasonically atomizing the deionized water, spray it onto the side of the first wet film not covered by the nonwoven fabric. The atomization time is 10s and the atomization volume is 10L·m -2 ·h -1 A glass plate is used to protect the nonwoven fabric side of the first wet film from contact with the mist droplets.

[0209] (3) The first wet film after spray treatment is immersed in a deionized water coagulation bath for 3 minutes for the first molding. After washing with deionized water, the support layer is obtained.

[0210] (4) Dissolve 0.5g of PDMS prepolymer, 0.4g of tetraethoxysilane, and 0.4g of dibutyltin dilaurate in 98.7g of n-heptane solvent, stir at 30°C to form a homogeneous solution, and degas under vacuum to obtain a second casting solution with a PDMS prepolymer concentration of 0.5wt%. Wet the support layer with deionized water, and then use a continuous coating machine to coat the second casting solution onto the side of the support layer not covered with nonwoven fabric to form a second wet film with a thickness of 2μm. Dry in a 30°C oven for 30min to obtain the composite film.

[0211] Example 10

[0212] (1) Dissolve 12g of polyacrylonitrile in 88g of N,N-dimethylformamide solvent, stir at 50℃ to form a homogeneous solution, and degas under vacuum to obtain the first casting solution. Use a continuous coating machine to coat the first casting solution onto a nonwoven fabric to form a first wet film with a thickness of 85μm.

[0213] (2) After ultrasonically atomizing the deionized water, spray it onto the side of the first wet film not covered by the nonwoven fabric. The atomization time is 15s and the atomization volume is 5L·m. -2 ·h -1 A glass plate is used to protect the nonwoven fabric side of the first wet film from contact with the mist droplets.

[0214] (3) The first wet film after spray treatment is immersed in a deionized water coagulation bath for 3 minutes for the first molding. After washing with deionized water, the support layer is obtained.

[0215] (4) Dissolve 0.5g of PDMS prepolymer, 0.4g of tetraethoxysilane, and 0.4g of dibutyltin dilaurate in 98.7g of n-heptane solvent, stir at 30°C to form a homogeneous solution, and degas under vacuum to obtain a second casting solution with a PDMS prepolymer concentration of 0.5wt%. Wet the support layer with deionized water, and then use a continuous coating machine to coat the second casting solution onto the side of the support layer not covered with nonwoven fabric to form a second wet film with a thickness of 2μm. Dry in a 30°C oven for 30min to obtain the composite film.

[0216] Example 11

[0217] (1) Dissolve 10g of polyacrylonitrile in 90g of N,N-dimethylformamide solvent, stir at 50℃ to form a homogeneous solution, and degas under vacuum to obtain the first casting solution. Use a continuous coating machine to coat the first casting solution onto a nonwoven fabric to form a first wet film with a thickness of 85μm.

[0218] (2) After ultrasonically atomizing the deionized water, spray it onto the side of the first wet film not covered by the nonwoven fabric. The atomization time is 5 seconds and the atomization volume is 10 L·m. -2 ·h -1 A glass plate is used to protect the nonwoven fabric side of the first wet film from contact with the mist droplets.

[0219] (3) The first wet film after spray treatment is immersed in a deionized water coagulation bath for 3 minutes for the first molding. After washing with deionized water, the support layer is obtained.

[0220] (4) Dissolve 3g of PDMS prepolymer, 1.5g of tetraethoxysilane, and 1.5g of dibutyltin dilaurate in 94g of n-heptane solvent, and stir at 30°C to form a homogeneous solution. Degas under vacuum to obtain a second casting solution with a PDMS prepolymer concentration of 3wt%. Wet the support layer with deionized water, and then use a continuous coating machine to coat the second casting solution onto the side of the support layer not covered with nonwoven fabric to form a second wet film with a thickness of 2μm. Dry in a 30°C oven for 30min to obtain the composite film.

[0221] Comparative Example 1

[0222] The composite membrane was prepared in accordance with the method of Example 1, except that no spraying treatment was performed.

[0223] Comparative Example 2

[0224] The composite membrane was prepared in accordance with the method of Example 1, except that no separation layer was coated.

[0225] Comparative Example 3

[0226] The composite membrane was prepared in accordance with the method of Example 1, except that the atomization time was 30 s.

[0227] Test Example 1

[0228] The support layer and composite film in the above embodiments and comparative examples were characterized using scanning electron microscopy.

[0229] Figure 1 The images shown are SEM images of the PAN support layer prepared in Example 1 of this invention. (a) is a surface SEM image, which shows that there is a nanoscale pore structure on the membrane surface; (b) is a cross-sectional SEM image, which shows that part of the cross-section has a finger-like pore structure and part has a mesh-like pore structure that appears after atomization treatment.

[0230] Figure 2 The images shown are SEM images of the composite membrane obtained in Example 1 of this invention. (a) is a surface SEM image, which shows that the surface of the composite membrane is smooth and flat without pores, indicating that the separation layer has been formed on the surface of the support layer. (b) is a cross-sectional SEM image, which shows the different layer structures of the composite membrane. The interlayer bonding is strong and there are no obvious defects, indicating that the composite membrane has been successfully obtained.

[0231] Figure 3 The images shown are SEM images of the PAN support layer prepared in Example 5 of this invention. (a) is a surface SEM image, which shows that there is a nanoscale pore structure on the membrane surface; (b) is a cross-sectional SEM image, which shows that part of the cross-section has a finger-like pore structure and part has a mesh-like pore structure that appears after atomization treatment.

[0232] Figure 4The images shown are SEM images of the composite membrane obtained in Example 5 of the present invention. (a) is a surface SEM image, which shows that the surface of the composite membrane is smooth and flat and without pores, indicating that the separation layer has been formed on the surface of the support layer; (b) is a cross-sectional SEM image, which shows the different layer structures of the composite membrane. The interlayer bonding is strong and there are no obvious defects, indicating that the composite membrane has been successfully obtained.

[0233] Figure 5 The images shown are SEM images of the PAN support layer prepared in Comparative Example 1 of this invention. (a) is a surface SEM image, which shows that there is a nanoscale pore structure on the membrane surface; (b) is a cross-sectional SEM image, which shows that the cross-section has a typical finger-like pore structure.

[0234] Figure 6 The image shows the SEM image of the PAN support layer prepared in Comparative Example 3 of this invention. In the image, (a) is the surface SEM image, which shows that there is a nanoscale pore structure on the membrane surface; (b) is the cross-sectional SEM image, which shows that the cross-section is a continuous mesh pore structure.

[0235] Figure 7 The image shown is a magnified SEM image of the cross-section of the PAN support layer prepared in Comparative Example 3, which further reveals the continuous mesh structure.

[0236] Figure 8 The nano-infrared spectrum (Nano-IR) of the PAN support layer and composite film prepared in this invention shows that at 1261 cm⁻¹... -1 (Bending vibration of Si-C), 1097 cm⁻¹ -1 (Asymmetric stretching vibration of Si-O-Si) and 1015 cm⁻¹ -1 The absorption peak at (symmetric stretching vibration of Si-O) is a characteristic peak of PDMS, indicating the presence of PDMS.

[0237] Test Example 2

[0238] Before coating the separation layer, the physicochemical parameters of the support layers obtained in the above examples and comparative examples were measured. After obtaining the composite membrane, the physicochemical parameters of the separation layer and the CO2 permeation rate and ideal CO2 / N2 separation coefficient of the composite membrane were measured.

[0239] The results are shown in Table 1.

[0240] Table 1

[0241]

[0242] Table 1 (continued)

[0243]

[0244]

[0245] Table 1 (continued)

[0246] <![CDATA[CO₂ permeation rate (GPU)]]> <![CDATA[CO2 / N2 ideal separation factor]]> Example 1 17208 11 Example 2 12586 10 Example 3 10750 10.5 Example 4 10129 10.8 Example 5 14334 10.3 Example 6 15177 10.5 Example 7 10560 11.6 Example 8 11727 10.3 Example 9 15340 9.6 Example 10 9920 13 Example 11 8430 13.6 Comparative Example 1 6615 6 Comparative Example 2 20000 1 Comparative Example 3 14700 2.6

[0247] As can be seen from the results in Table 1, the composite membrane preparation method provided by the present invention can improve the connectivity density of the support layer, enhance the interfacial bonding force between the support layer and the separation layer, and reduce the overall thickness of the composite membrane by spraying the first wet membrane, so that the composite membrane can significantly improve the CO2 permeation flux while maintaining high selectivity.

[0248] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A composite membrane, characterized in that, The composite membrane comprises a support layer and a separation layer arranged sequentially. The support layer has an average pore size of 20-120 nm and a volumetric porosity of 40-70%. The connectivity density of the support layer is 6×10⁻⁶. 15 -9×10 15 m -3 .

2. The composite membrane according to claim 1, characterized in that, The connectivity density of the support layer is 6.5 × 10⁻⁶. 15 -8.5×10 15 m -3 ; Preferably, the D of the support layer 10 Aperture is 19-39 nm, D 50 Aperture is 40-95nm, D 90 The pore size is 100-150 nm; Preferably, the volumetric porosity of the support layer is 50-60%; Preferably, the thickness of the support layer is 10-60 μm.

3. The composite membrane according to claim 1 or 2, characterized in that, The thickness of the separation layer is 100-400 nm; Preferably, the average roughness of the separation layer surface is 5-10 nm; Preferably, the water contact angle of the separation layer is 100-115°; Preferably, the CO2 permeation rate of the composite membrane is 10,000-18,000 GPU, and the ideal CO2 / N2 separation coefficient is 9-13.

4. The composite membrane according to any one of claims 1-3, characterized in that, The support layer is selected from at least one of polysulfone, polyethersulfone, polyacrylonitrile, cellulose acetate, polyvinylidene fluoride, polyimide, polyacrylic acid, polylactic acid, polyamide, polyetherimide, polystyrene, polyolefin, and polyester; And / or, the separation layer is polysiloxane and / or polysilyne.

5. A method for preparing a composite membrane, characterized in that, The method includes the following steps: (1) Apply a first casting solution containing a support layer material to form a first wet film; (2) Spray one side of the first wet film for 1-25 seconds; (3) The first wet film after spray treatment is first shaped to obtain a support layer; (4) A second casting solution containing a separation layer material prepolymer, an organotin catalyst and a coupling agent is coated on the side of the support layer that has been sprayed to form a second wet film, and a second molding is performed to obtain the composite film.

6. The method according to claim 5, characterized in that, The method further includes: pre-filling the side of the support layer that has been sprayed with a filling liquid before applying the second casting liquid; Preferably, the filling liquid is selected from at least one of water, lower alcohols, lower ethers, N-methylpyrrolidone and N,N-dimethylformamide.

7. The method according to claim 5 or 6, characterized in that, In step (1), the support layer material is selected from at least one of polysulfone, polyethersulfone, polyacrylonitrile, cellulose acetate, polyvinylidene fluoride, polyimide, polyacrylic acid, polylactic acid, polyamide, polyetherimide, polystyrene, polyolefin, and polyester. Preferably, the thickness of the first wet film is 70-100 μm; Preferably, the concentration of the support layer material in the first casting solution is 6-15 wt%.

8. The method according to any one of claims 5-7, characterized in that, In step (2), the atomization rate of the spray treatment is 2.5-20 L·m -2 ·h -1 ; Preferably, the liquid used in the spray treatment is a non-solvent of the support layer material.

9. The method according to any one of claims 5-8, characterized in that, In step (4), the prepolymer of the separation layer material is a polysiloxane prepolymer and / or a polysilyne prepolymer; Preferably, the organotin catalyst is selected from at least one of dibutyltin diacetate, dibutyltin dilaurate, and stannous octoate; Preferably, the coupling agent is selected from at least one of γ-aminopropyltriethoxysilane, vinyltrimethoxysilane, tetraethoxysilane, methyltriethoxysilane, and propyltriethoxysilane; Preferably, the concentration of the prepolymer of the separation layer material in the second casting solution is 0.2-2 wt%. Preferably, the thickness of the second wet film is 1-3 μm.

10. A composite membrane prepared by the method of any one of claims 5-9.

11. The application of the composite membrane according to any one of claims 1-4 and 10 in gas separation.

Citation Information

Patent Citations

  • Composite film prepared from acryloyloxy-terminated PDMS (polydimethylsiloxane) as well as preparation method and application of composite film

    CN115155331A

  • Polyether block polyamide / polydimethylsiloxane composite gas separation membrane, preparation method and application

    CN115608177A